Communicating with Inpatients with Memory Impairments - Valitchka, Lindsey; Turkstra, Lyn S. (Seminars in Speech and Language, 2013)
Many patients with acquired brain injury have acute impairments in declarative memory, the memory system responsible for learning facts and remembering events, whereas implicit memory for skills, habits, and emotional associations remains intact. The combination of impaired declarative memory and preserved implicit memory has implications for communicating with patients in inpatient rehabilitation, not only in therapy sessions but also in nontherapy interactions with rehabilitation staff. The aim of this study was to describe communication patterns among inpatients with declarative memory impairments and rehabilitation staff members during the early stage postinjury. Participants were five adults with acquired brain injury and declarative memory impairments. Each participant was observed for a full inpatient rehabilitation day. Results showed that staff and visitors frequently asked participants declarative questions to which answers were not verifiable (e.g., questions about preinjury events). Answers that could be verified often were incorrect but were accepted by staff as correct. Results suggest that acute rehabilitation staff may need training in communicating with patients with declarative memory impairments. We suggest strategies to create a more supportive communication environment for inpatients with memory impairment.
Keywords: Communication; memory; posttraumatic amnesia; inpatient rehabilitation; cognitive rehabilitation